Risk factors for candidaemia in a Malaysian tertiary hospital - Tzar, M.N.; Norazlah, B.; Shamsul, A.S. (Universiti Kebangsaan Malaysia, 2015)
Candidaemia carries high morbidity and mortality, but its conventional diagnosis is time consuming and insensitive. Clinical risk factors may identify suitable candidates for prophylactic or pre-emptive antifungal therapy and may be modified or controlled to prevent candidaemia. Therefore, this study aimed to identify the independent risk factors for candidaemia. The study was a retrospective, case-control study involving 54 patients with candidaemia and 54 patients without candidaemia as controls. The patient’s data were collected from the medical records and the risk factors for candidaemia were analyzed in both groups. Candida species isolated from blood were C. tropicalis (n=19, 35.2%), C. albicans (n=18, 33.3%), C. parapsilosis (n=11, 20.4%) and one isolate each (1.9%) of C. famata, C. glabrata, C. krusei, C. melibiosica, C. pelliculosa and C. sake. Multivariate analysis showed that renal insufficiency, prior antibacterial therapy, prior antifungal therapy, steroid therapy and urinary catheterization were independent risk factors for candidaemia. Central venous catheter, prolonged hospital stay, intensive care unit stay, mechanical ventilation, surgery and parenteral nutrition occurred more commonly among the candidaemia group but were not independently significant. Controlling, limiting or modifying these risk factors may reduce the incidence of candidaemia.